1997
DOI: 10.1046/j.1365-294x.1997.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity, reproductive isolation and host preferences in mealy aphids of the Hyalopterus pruni complex (Homoptera, Aphidoidea)

Abstract: Three taxa were detected by allozyme markers within the mealy aphids of the Hyalopterus pruni complex, having different cultivated Prunus species as main primary hosts. The genetically closer H. pruni and H. amygdali A (DNei= 0.10) never share primary hosts, whereas H. amygdali A and B (DNei= 0.32) may occasionally share them, producing few F1 hybrids. The three species proved reproductively isolated in the field, with no gene exchange. Their speciation seem to have occurred long before the agricultural revolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 9 publications
8
35
2
Order By: Relevance
“…Based on allozyme data from Italian populations, Spampinato et al (1988) suggested that H. pruni is genetically distinct and H. amygdali is heterogeneous. This was confirmed by an extensive study of Italian and Sicilian populations of the taxa using allozyme markers (Mosco et al, 1997). These authors detected three taxa: the genetically close H. pruni and H. amygdali A and H. amygdali B. Hyalopterus pruni was collected from plum, apricot, and less frequently from blackthorn, Prunus spinosa L., cherry plum, Prunus cerasifera (Ehrh.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Based on allozyme data from Italian populations, Spampinato et al (1988) suggested that H. pruni is genetically distinct and H. amygdali is heterogeneous. This was confirmed by an extensive study of Italian and Sicilian populations of the taxa using allozyme markers (Mosco et al, 1997). These authors detected three taxa: the genetically close H. pruni and H. amygdali A and H. amygdali B. Hyalopterus pruni was collected from plum, apricot, and less frequently from blackthorn, Prunus spinosa L., cherry plum, Prunus cerasifera (Ehrh.…”
Section: Introductionmentioning
confidence: 68%
“…However, the present study targets taxa in which there is already evidence of host-associated genetic variation and reproductive isolation (Spampinato et al, 1988;Mosco et al, 1997). Generally, the three host-associated morphologically distinct groups found accord with the results of Mosco et al (1997).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…35.-According to Kadyrbekov (2001b) (Barbagallo et al, 1998;Lampel, 1968). The apterous fundatrigeniae (parthenogenetic females living on the primary host) are very difficult to differentiate morphologically (Basky & SzalayMarszó, 1987;Blackman & Eastop, 2000), even without considering genetic differences between two forms of H. amygdali: "form A" and "form B" (Mosco et al, 1997), whereas it seems possible to differentiate them by the bionomical criterion of the host plant. It is not possible to differentiate the apterous virginogeniae (parthenogenetic females living on the secondary host) and all the alatae females by morphological criteria in the light of data available at present and they can only be identified by plant transfer tests or by relating located populations to the trees where the alate fundatrigeniae emigrated from.…”
Section: The Iberian-balearic Check-list Of Species and Subspecies Bementioning
confidence: 99%